Fixed Drug Eruption Likely Triggered by Antitubercular Drugs During Tuberculosis Treatment: A Case Report - Jha, Ambika Nand; Gaikwad, Varsha Ratan (Bangladesh Journal of Infectious Diseases, 2025)
Tuberculosis (TB) remains a major global health challenge, contributing significantly to mortality rates around the world. Treatment with anti-TB first line drug can frequently lead to side effects Hepatotoxicity, GI Discomfort & skin rashes but the severe skin reaction are uncommon. A 38-year-old male patient presented to a private clinic with concerns about painful, fluid-filled skin lesions that were also causing significant itching. These symptoms began to manifest 7 weeks following the initiation of anti-tubercular treatment (ATT). The patient sought medical attention due to the persistent and distressing nature of these skin issues, which had become a prominent concern alongside his ongoing treatment regimen. The presentation of these symptoms raised the possibility of a drug-induced reaction, necessitating a thorough evaluation to determine the cause and appropriate management of his condition. Fixed drug eruptions can be linked to various medications. But there were limited literature available about ATT induce fixed drug eruptions It is important to remain vigilant for such reactions during anti-tubercular therapy (ATT), as current attention is primarily on hepatotoxicity and neurotoxicity. We should also include this type of reaction in our clinical evaluations to ensure a comprehensive assessment of potential adverse effects. Bangladesh Journal of Infectious Diseases, December 2024;11(2):209-213